Strategi Bauran Promosi (Promotional Mix) Untuk Meningkatkan Minat Beli Konsumen Dan Jumlah Reseller Di Desa Kamal (Studi Kasus Pada PT. QUEEN ICE Di Bangkalan Madura) - Rethna Anggun Gumylang; Mohamad Thambrin (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
This study aims to determine the promotional mix strategy. This research was conducted at PT. Queen Ice Asia Bangkalan Madura, as well as consumers and resellers in Kamal village, the implementation of this research was started from September 2020 to January 2021. This study used a qualitative descriptive research approach. The instrument used in this study was in the form of data from observations made by the researcher as the observer, then the researcher conducted interviews to get more accurate data and maximum results. The research is also equipped with documentation during the observation and interview process. After the researcher conducts observation and interview activities, it can be seen that there has been an increase and success in the promotion process by using the existing promotional mix. In addition, it can also be seen the advantages and constraints of using the company's promotional mix strategy.